Successful field performance in warm and dry environments of soybean expressing the sunflower transcription factor HB4. (6th March 2020) - Ribichich, Karina F; Chiozza, Mariana; Ávalos-Britez, Selva; Cabello, Julieta V; Arce, Augustin L; Watson, Geronimo; Arias, Claudia; Portapila, Margarita; Trucco, Federico; Otegui, Maria E; Chan, Raquel L
Abstract: Soybean yield is limited primarily by abiotic constraints. No transgenic soybean with improved abiotic stress tolerance is commercially available. We transformed soybean plants with genetic constructs able to express the sunflower transcription factor HaHB4, which confers drought tolerance to Arabidopsis and wheat. One line (b10H) carrying the sunflower promoter was chosen among three independent lines because it exhibited the best performance in seed yield, and was evaluated in the greenhouse and in 27 field trials in different environments in Argentina. In greenhouse experiments, transgenic plants showed increased seed yield under stress conditions together with greater epicotyl diameter, larger xylem area, and increased water use efficiency compared with controls. They also exhibited enhanced seed yield in warm and dry field conditions. This response was accompanied by an increase in seed number that was not compensated by a decrease in individual seed weight. Transcriptome analysis of plants from a field trial with maximum difference in seed yield between genotypes indicated the induction of genes encoding redox and heat shock proteins in b10H. Collectively, our results indicate that soybeans transformed with HaHB4 are expected to have a reduced seed yield penalty when cultivated in warm and dry conditions, which constitute the best target environments for this technology. Abstract : HaHB4 transgenic soybean plants significantly outyielded controls in warm and dry environments, showing increased seed number, xylem area, and water use efficiency, and induction of genes encoding redox and heat shock proteins.